Variabel-variabel yang memengaruhi Status Overeducation pada Tenaga Kerja Terdidik di Jawa Barat - Rini Rahani; Siti Asiah; Aldilla Pramudita Caesar (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
The inability of the labor market in West Java to absorb educated workers has led to the phenomenon of overeducation. Overeducation occurs when the educational level of the workers is higher than the level required for the job. This issue needs to be addressed so that educated workers can secure better jobs and increase productivity. This study aims to provide an overview of the overeducation status, the influence of individual and regional variables, and their tendencies on the overeducation status of educated workers in West Java Province. The data used comes from the raw data of the National Labor Force Survey (Sakernas) August 2022, the publication on the Worker’s Situation in West Java Province, and the website of the DPMPTSP West Java Province. The statistical method used is multilevel binary logistic regression analysis with a random intercept. The results showed that 40.22 percent of educated workers in West Java experience overeducation. The tendencies of overeducated educated workers in West Java in 2022 include being male, university graduates, lacking ICT skills, having no employment contract, residing in rural areas, and living in regencies/cities with low employment rates in the industrial and service sectors. Several policy recommendations are provided to the government to address the issue of overeducation among educated workers in West Java.